2001
DOI: 10.1172/jci10564
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal expression in hyaline cartilage of constitutively active human collagenase-3 (MMP-13) induces osteoarthritis in mice

Abstract: IntroductionDegenerative joint diseases including osteoarthritis (OA) are common, particularly in the elderly. Early signs of OA include progressive loss from articular cartilage of the proteoglycan aggrecan, reflected by a loss of safranin O staining, excessive damage to type II collagen, and general degeneration and fibrillation of the cartilage surface, resulting ultimately in a loss of articular cartilage (1).One of the primary targets of this disease is type II collagen, the major structural collagen foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
351
1
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 503 publications
(370 citation statements)
references
References 46 publications
13
351
1
5
Order By: Relevance
“…Our finding that two collagenases implicated in cartilage collagen hydrolysis, collagenase-1 and collagenase-3 [51][52][53][54] were not potently inhibited by EGCG and ECG, is evidence that this is not via direct inhibition of these collagen-degrading enzymes. Other mechanisms are possible, including effects on proinflammatory signalling pathways.…”
Section: Discussionmentioning
confidence: 67%
“…Our finding that two collagenases implicated in cartilage collagen hydrolysis, collagenase-1 and collagenase-3 [51][52][53][54] were not potently inhibited by EGCG and ECG, is evidence that this is not via direct inhibition of these collagen-degrading enzymes. Other mechanisms are possible, including effects on proinflammatory signalling pathways.…”
Section: Discussionmentioning
confidence: 67%
“…*indicates significant differences with respect to cells co-transfected with the MMP-13 promoter and the p65/p50 expression vectors (P \ 0.05) MMP-13, in articular chondrocytes are known to promote the cleavage of collagen triple helices allowing further degradation by other MMPs (Nagase and Woessner 1999). Supporting the role of MMP-13 in connective tissue degradation, Neuhold et al (2001) reported that transgenic mice overexpressing MMP-13 show signs of articular cartilage degradation and exhibit joint pathology similar to that found in OA. Our results confirm that IL1b represents a potent inflammatory stimulus that leads to overexpression of MMP-1, MMP-3, and MMP-13 mRNA in primary and SW1353 chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our strategy for development of DMOADs was to focus on identification of highly selective allosteric MMP-13 inhibitors free of hydroxamic acid or other zinc-chelating functional groups that contribute to inhibition of multiple MMPs. The rationale for targeting MMP-13 came from 1) overwhelming data on a potential role of MMP-13 in the pathogenesis of OA (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), and 2) data from studies of MMP-13 knockout mice and humans with an MMP-13 mutation, suggesting lack of MSS liability (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…It cleaves the triple-helical collagen at a unique site, resulting in a three-quarter-length and a one-quarter-length product (11,12,18). Data on MMP-13-transgenic animals indicate that MMP-13 induces joint abnormalities characteristic of human OA (19). Moreover, semiselective MMP-13 inhibitors block degradation of human OA cartilage cultures (20).…”
mentioning
confidence: 99%